2016
DOI: 10.1167/iovs.16-19520
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Macular Pigment Enhances Contrast Sensitivity in Subjects Free of Retinal Disease: Central Retinal Enrichment Supplementation Trials – Report 1

Abstract: METHODS. Subjects consumed daily a formulation containing 10 mg L, 2 mg Z, and 10 mg MZ (active group; n ¼ 53) or placebo (n ¼ 52) for a period of 12 months. Study visits were at baseline, 3, 6, and 12 months. Contrast sensitivity at 6 cycles per degree (cpd) was the primary outcome measure (POM). Secondary outcome measures included CS at other spatial frequencies, best-corrected visual acuity (BCVA), glare disability, photostress recovery, and light scatter. Macular pigment optical density (MPOD) was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
87
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 58 publications
(57 reference statements)
9
87
2
1
Order By: Relevance
“…In the current study, significant increases in CS were observed at spatial frequencies of 6 and 18 cpd after L+Z+DHA supplementation, consistent with previous studies showing positive effects of L+Z or L+Z+MZ supplementation on CS 10,3234. These findings have potentially important implications with respect to the preservation of visual performance in individuals with AMD because low CS is highly predictive of poor vision 32.…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, significant increases in CS were observed at spatial frequencies of 6 and 18 cpd after L+Z+DHA supplementation, consistent with previous studies showing positive effects of L+Z or L+Z+MZ supplementation on CS 10,3234. These findings have potentially important implications with respect to the preservation of visual performance in individuals with AMD because low CS is highly predictive of poor vision 32.…”
Section: Discussionsupporting
confidence: 91%
“…In terms of visual performance, the antioxidant potential of the MCs would appear to impact outcome measures that are particularly dependent on metabolic processes, such as dark adaptation [6, 7], contrast sensitivity [812], and temporal vision [13, 14]. Due to its location being anterior to the photoreceptors [15] and aforementioned yellow-orange coloration [16], most of the previous work involving macular carotenoids and visual performance has involved the short-wavelength filtering properties of MP, however.…”
Section: Introductionmentioning
confidence: 99%
“…These effects, however, appear to be dependent on the presence of an appreciable short-wavelength component in the glare source [22], such as that found in the solar spectrum. For example, a recent investigation of visual performance after augmentation of MP optical density (MPOD) with MC supplementation determined significant improvements in contrast sensitivity, but not PSR [12]. A bright, tungsten source was used as the photostressor in that study, and may not have contained a sufficient amount of short-wavelength energy to reveal effects of MP’s filtering.…”
Section: Introductionmentioning
confidence: 99%
“…Despite optimal control of blood glucose and advances in the treatment of diabetic eye disease, the prevalence rate of DR in the USA have increased considerably over the last decade 88. Experimental studies in animal models provide strong support in favour of oxidative damage in the aetiopathogenesis of DR.…”
Section: Discussionmentioning
confidence: 99%
“…The reason is that the highest concentration of L and Z within the retina corresponds with the anatomical site of the disease process (ie, macula) in the form of MP. And, there is evidence-based consensus that MP is important for optimal visual performance because of its blue light filtering properties and consequential attenuation of chromatic aberration, veiling luminance, glare disability and blue haze 88. Moreover, MP can be measured in the human eye using subjective or objective non-invasive techniques.…”
Section: Discussionmentioning
confidence: 99%